A novel variant c.7104 + 6T > A of ABCA12 linked to autosomal recessive congenital ichthyosis verified by minigene splicing assay - Zhu, Linyan; Zhou, Rui; Zhang, Lianxiao; Chen, Mei; Zhang, Shengmin; Huang, Xiaxi; Shi, Yubo; Ding, Huiqing (Frontiers in Pediatrics, 2024)
Background Autosomal recessive congenital ichthyosis (ARCI) is a group of genetic skin disorders characterized by abnormal keratinization, leading to significant health issues and reduced quality of life. ARCI encompasses harlequin ichthyosis (HI), congenital ichthyosiform erythroderma (CIE), and lamellar ichthyosis (LI). While all ARCI genes are linked to LI and CIE, HI is specifically associated with severe mutations in the ABCA12 gene. Milder forms like LI and CIE usually involve at least one non-truncating ABCA12 variant. Methods Whole-exome sequencing (WES) was performed on fetal and parental DNA, and ABCA12 gene variants were validated by Sanger sequencing. The functional effect of the novel variant c.7104+6T>A was evaluated using an in vitro minigene system, with splicing analysis conducted via PCR and Sanger sequencing. Results A compound heterozygous variation in the ABCA12 gene, comprising c.5784G>A (p.W1928*) and c.7104+6T>A, was identified in the fetus, inherited from the father and mother, respectively. According to ACMG guidelines, the c.7104+6T>A variant is classified as a Variant of Uncertain Significance (VUS). Computational predictions suggested that this variant affects splicing. A minigene assay further confirmed that the c.7104+6T>A variant in ABCA12 leads to two types of aberrant mRNA splicing: a 69-base pair deletion (c.7036_7104del, p.Val2346_Glu2368del) and skipping of Exon 47, both of which result in a premature stop codon and a truncated protein. Conclusion In conclusion, this study identified a novel genetic variant, c.7104+6T>A in ABCA12, as the cause of ARCI in a fetus, thereby enriched the known ABCA12 mutation spectrum.